Efficiency of Modified Zeolite with Cationic Surfactant Hexadecyltrimethylammonium Bromide in Removal of Diazinon from Aqueous Solutions - Ramzanali Dianati Tilaki; jamshid yazdani charati; sahebeh bavandi (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Diazinon is one of the most widely used pesticides in agricultural pest control that pollutes water resources. The aim of this study was to evaluate the adsorption of diazinon from water by zeolite modified with cationic surfactant hexadecyltrimethyl ammonium bromide (HDTMA). Materials and methods: The amount of HDTMA surfactant used to modify the zeolite was one-fold External Cation Exchange Capacity (ECEC) of zeolite (0.53 mmol/g). Modification was performed by contacting zeolite and surfactant for 24h on the shaker. Unmodified and modified zeolite were tested as adsorbent. Experiments were conducted in batch mode in acidic (pH=3), natural (pH=7), and alkaline conditions (pH=11). Results: The optimal contact times for adsorption of diazinon were 10 and 5 minutes on unmodified zeolite and HDTMA-modified zeolite (HMZ), respectively. According to the Freundlich model, the amount of diazinon absorbed by the HMZ was about 8 times more than that of the unmodified zeolite. By using 1gl-1 of HMZ at pH= 3, the maximum adsorption was 97.6%. Pseudo second order kinetics and Freundlich isotherm model well describes the absorption of diazinon on HMZ. Conclusion: Modified zeolite has high capacity, so, the method used here, can be used to increase the efficiency of diazinon adsorption in wastewater treatment plants.